The Influence of Corporate Purpose on Directors' Interpretations of their Duty to Act in Good Faith and in the Best Interests of the Company - Buckley, Lynn (Victoria University of Wellington Law Review, 2025)
Does a corporation's purpose influence its directors' interpretations of their duty to act in good faith and in the best interests of the company? To consider this question, this article explores interview data generated with 22 professional directors sitting on private sector boards in Aotearoa New Zealand. These professional directors held board roles across 92 private sector companies, 24 of which are NZX/ASX-listed and 49 defined as large under the Financial Reporting Act 2013. The interview findings reveal that director interpretations of the duty are often influenced by their understanding of their corporation's purpose. This insight may have meaningful implications for the implementation of corporate purpose, given that the duty is fundamental and operates ex ante when directors are making business decisions.